2021
DOI: 10.1002/ajhb.23675
|View full text |Cite
|
Sign up to set email alerts
|

Body adiposity measures and risk of adolescent hypertension among the postpubescents Northeast India

Abstract: Objectives The present study attempts to associate and predict adolescent hypertension in Northeast India through body adiposity measures. Method A total of 728 adolescents aged 15 years and above were included in the present study after consent. Blood pressure and related anthropometric data were collected. The prevalence rate was calculated. Significant tests and correlation analyses were conducted between the blood pressure parameters and anthropometric body adiposity measures. The odds ratio (OR) was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The overall prevalence of prehypertension and hypertension in adolescents was 24.5% in another school-based study done in rural Kerala by Amma et al [ 15 ]. The prevalence of adolescent hypertension was 29.12%, and elevated blood pressure was 20.47% as per the AAP criteria in another study from northeast India which was done among adolescents aged equal to or more than 15 years by Meitei et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall prevalence of prehypertension and hypertension in adolescents was 24.5% in another school-based study done in rural Kerala by Amma et al [ 15 ]. The prevalence of adolescent hypertension was 29.12%, and elevated blood pressure was 20.47% as per the AAP criteria in another study from northeast India which was done among adolescents aged equal to or more than 15 years by Meitei et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on adolescent hypertension from India as well as abroad have also reported similar associations. A study from northeast India found that overweight, obesity, and abdominal volume index (AVI) has 2.31, 5.15, and 3.41 OR to develop hypertension significantly, irrespective of gender [ 16 ]. Amma et al observed that overweight or obese adolescents had 5.7 times more risk of developing hypertension than normal or underweight adolescents [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies show that sedentary behavior is associated with adiposity 29,30 and adiposity is related to BP, 31,32 only a few have studied the association between ST and BP. Guillaume et al 33 found a positive association between TV viewing and systolic BP in 6 to 12-year-old Belgium boys.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in western countries report that prevalence of hypertension in children is around 7-19% [4]. Hitherto, the highest national reported figure of adolescent hypertension and elevated blood pressure, being 29.12% and 20.47%, respectively, was reported by Meitei et al [5] from the population of Northeast India.…”
Section: Introductionmentioning
confidence: 90%